Assessing the efficacy of cash incentive policies in enhancing remittance inflows: Evidence from Bangladesh - Muhammad Nafis Shahriar Farabi; Mahadee Al Mobin; Asir Newaz Khan (PLoS ONE, 2025)
The Government of Bangladesh (GoB) first implemented the cash incentive of 2 percent in July 2019 and continued the scheme with some modifications amid the pandemic to enhance remittance inflows through formal channels and ensure macroeconomic stability in the country. This study examines the impact of the cash incentive introduced by the GoB to boost remittance inflow using the Interrupted Time Series (ITS) analysis along with the Chow test for structural stability. While ITS analysis has been employed by numerous studies in the healthcare sector, but this paper uses such analysis for the first time in any type of migration study in Bangladesh. We have used ITS as it is most effective in measuring the impact of policy interventions that are expected to act either quickly after an intervention or within a stipulated time frame. The study is also the first to examine the region wise efficacy of policy intervention in the country. Monthly Remittance Inflow data from July 2013 to December 2021 has been used for the analysis. Chow test results conclude that the policy intervention had a significant impact while the ITS analysis findings demonstrated that the cash intervention significantly increased both aggregated and region-specific remittance inflows, highlighting the significance of the action. The overall findings revealed that the introduction of cash incentive in July 2019 resulted in an immediate, sustained increase of 6.68 percent in remittance inflows, with a further increase of 0.25 percent every month. Region wise analysis shows that the impact was highest in the USA & UK region and lowest in the Middle Eastern region, which signifies issues related to prevalence of hundi market, skillset of migrant workers, average monthly salary, and remittance sending costs. Our research provides policymakers with significant information to implement customized policies that ensure macroeconomic stability by enhancing remittance inflows through formal channels.